2019
DOI: 10.3847/1538-4357/ab0824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dark Matter–Dark Radiation Interactions on Halo Abundance: A Press–Schechter Approach

Abstract: We study halo mass functions with the Press-Schechter formalism for interacting dark matter models, where matter power spectra are damped due to dark acoustic oscillations in the early universe. After adopting a smooth window function, we calibrate the analytical model with numerical simulations from the "effective theory of structure formation" (ETHOS) project and fix the model parameters in the high mass regime, M h 3 × 10 10 M . We also perform high-resolution cosmological simulations with halo masses down … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 95 publications
2
23
0
Order By: Relevance
“…It has been widely discussed in the literature that SIDM preserves the predictions of CDM on the scales larger than galaxies (e.g. see Rocha et al 2013;Vogelsberger et al 2016;Sameie et al 2019). In this section, we discuss the impact of SIDM on the overall features of galaxies embedded in their DM haloes.…”
Section: Mass Assembly and Star Formation Ratementioning
confidence: 91%
“…It has been widely discussed in the literature that SIDM preserves the predictions of CDM on the scales larger than galaxies (e.g. see Rocha et al 2013;Vogelsberger et al 2016;Sameie et al 2019). In this section, we discuss the impact of SIDM on the overall features of galaxies embedded in their DM haloes.…”
Section: Mass Assembly and Star Formation Ratementioning
confidence: 91%
“…B2). Sameie et al (2019) matched ODM simulations with (𝛽 = 3.7, 𝑐 = 3.5). We found that a slightly smaller value of 𝛽 = 3 (blue solid line) was necessary to fit the smoothed oscillation (see bottom right panel of Fig.…”
Section: Appendix C: Comparison Of Our Press-schechter Parametrizatio...mentioning
confidence: 99%
“…The Press-Schechter approach can be readily extended to provide a reasonable approximation to the halo mass function in these models as well [e.g. [115][116][117]. Fig.…”
Section: The Structural Properties Of Dark Matter Haloesmentioning
confidence: 99%